The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/6108575
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosusReduces Blood Glucose Level through Downregulation of Gluconeogenesis Gene Expression in Streptozotocin-Induced Diabetic Rats

Abstract: Some lactic acid bacteria (LAB) are observed to be potential probiotics with functional properties such as lowering fasting blood glucose (FBG), as a promising hyperglycemia management. This study investigated the ability and mechanism of Lactobacillus rhamnosus BSL and Lactobacillus rhamnosus R23 on lowering FBG in diabetic rats induced by streptozotocin (STZ). The rats were orally administered with L. rhamnosus BSL and L. rhamnosus R23 by giving 1 mL cell suspension (109 CFU/mL) daily for 30 days. The body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
(86 reference statements)
2
24
0
4
Order By: Relevance
“…Lactobacillus has been used to improve glucose tolerance independent of weight loss in db/db mice, 34 and, more recently, oral supplementation with Lactobacillus rhamnosus has reduced gluconeogenesis and improved hyperglycemia in diabetic rats. 35 The reduction in glucose tolerance in recipient mice is interesting given that obese donors did not display elevations in fasting glucose or in HbA1C, a marker of chronic glucose levels. These data align with those by Vrieze et al, who demonstrated that transfer of gut microbiota from lean human donors to individuals with metabolic syndrome increased insulin sensitivity in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus has been used to improve glucose tolerance independent of weight loss in db/db mice, 34 and, more recently, oral supplementation with Lactobacillus rhamnosus has reduced gluconeogenesis and improved hyperglycemia in diabetic rats. 35 The reduction in glucose tolerance in recipient mice is interesting given that obese donors did not display elevations in fasting glucose or in HbA1C, a marker of chronic glucose levels. These data align with those by Vrieze et al, who demonstrated that transfer of gut microbiota from lean human donors to individuals with metabolic syndrome increased insulin sensitivity in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Additionally, supplementation of Lactobacillus may benefit T1D www.advancedsciencenews.com www.mnf-journal.com patients. [24] There are several proposed mechanisms through which Lactobacillus improves glucose metabolism, including decreasing inflammatory status, improving insulin signaling, and SCFAs production. [25][26][27] In this study, we did find that goat milk consumption (at 5 and 10 g kg −1 doses) decreased the levels of TNF-, which is an indicator of inflammatory status (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…L. rhamnosus BSL and L. rhamnosus R23, when administered in STZ-induced diabetic Sprague-Dawley rats, led to elevated LAB levels after 30 days of probiotic supplementation and improved glucose tolerance and glucose control, as FBG was significantly reduced. After probiotic treatment, there was a decrease in TC and in atherogenic index [ 130 ].…”
Section: Functional Foods and Diabetesmentioning
confidence: 99%